2019
DOI: 10.1016/j.jstrokecerebrovasdis.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Trajectory, and Predictors of Poststroke Fatigue among Ghanaians

Abstract: Background & Purpose: Post-stroke fatigue (PSF) is rife among stroke survivors and it exerts a detrimental toll on recovery from functional deficits. The burden of PSF is unknown in sub-Saharan Africa. We have assessed the prevalence, trajectory and predictors of PSF among 60 recent Ghanaian stroke patients.Methods: Study participants in this prospective cohort (recruited between January/2017 and June/2017) were stroke survivors, aged >18 years, with CT scan confirmed stroke of less than 1month onset. PSF was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…The most failed criterion was appropriate sampling as only two papers had a representative sample, with either a population-based or randomised sample, whereas the majority had a consecutive sampling. 37,38 All studies reported a cut-off point of four or more to identify fatigued participants. There was only one study that exclusively included participants with severe fatigue and reported a PSF prevalence of 92%, as a result, it was not included in the final quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The most failed criterion was appropriate sampling as only two papers had a representative sample, with either a population-based or randomised sample, whereas the majority had a consecutive sampling. 37,38 All studies reported a cut-off point of four or more to identify fatigued participants. There was only one study that exclusively included participants with severe fatigue and reported a PSF prevalence of 92%, as a result, it was not included in the final quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Another possible reason is studies’ use of different fatigue scales, with varying classifications of fatigue. Notably, stroke survivors with depressive symptoms are at a significantly higher risk of experiencing fatigue (adjusted odds ratio = 8.86) [ 52 ]. Fatigue is also significantly correlated with anxiety and cognitive functioning in stroke survivors [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most data on stroke complications in Africa come from hospital-based studies and suggest that some form of complication occurs in >80% of inpatients with stroke (Table 2 ). Stroke complications in Africa include delirium 159 161 , post-stroke aspiration pneumonia 85 , 86 , 162 – 166 , bacteriuria and urinary tract infection 167 169 , aphasia and deglutition disorders 170 , anxiety 99 , 171 173 , fatigue 174 176 , sexual dysfunction 177 179 , pain (central post-stroke pain syndrome) 180 183 , depressive illness 184 193 and cognitive impairment that often leads to dementia 194 – 197 .…”
Section: Stroke Phenotypes In Africamentioning
confidence: 99%